Relationship between Coral Fish Community Structure with Chlorophyll-A Content and Sea Surface Temperature in the Conservation Area Suaka Alam Perairan (SAP) Raja Ampat, West Papua - Muhammad Rizky Adipratama; Mauludiyah Mauludiyah; Dian Sari Maisaroh; Wiga Alif Violando; Ofri Johan; Idris; Paryono; Sadikin Amir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The The waters of Raja Ampat have a healthy coral reef ecosystem and a wide variety of species so it has a high abundance of coral reef fish. One of the indicators of fertility level in water is chlorophyll-a and its high and low are influenced by sea surface temperature. The purpose of this study was to determine the relationship between chlorophyll-a content and sea surface temperature using satellite imagery data on the community structure of reef fish in the waters of SAP Raja Ampat. The coral reef fish data collection method used UVC (Underwater Visual Census) while the chlorophyll-a content and sea surface temperature used spatial analysis. The results showed that the reef fish diversity index value was 4,1 - 4,6 in the high category, uniformity 0,88-0,96 in the high category, dominance 0,014 - 0,026 in the low category, for abundance 244.340 ind/ha – 403.520 ind/ha and biomass 131,45 kg/ha - 204 kg/ha. The chlorophyll-a content obtained was 0,366 mg/m3 – 0,511 mg/m3 and the sea surface temperature obtained was 30,717°C – 31,899°C. The results of the relationship of reef fish community structure with chlorophyll-a content and sea surface temperature do not have a significant correlation.